Study on Spatial Temporal Distribution Characteristics of Air Quality Index in Beijing and Its Correlation with Local Meteorological Conditions - Jiaqi Guo; Zhongke Feng (Discrete Dynamics in Nature and Society)
The changing of AQI presented by historical observations has significant meaning to the urban air pollution prevention. In order to explore the correlation between air quality and meteorological condition in Beijing from 2014 to 2017, researchers processed 52165 sample data from 35 air monitor stations by means of R statistical software, analyzed the spatial temporal distribution characteristics of air quality index (AQI) with Kriging and mathematical statistics and did the research on correlation between spatial temporal distribution characteristics of AQI and meteorological condition. The results showed that (1) the spatial increasing trend of AQI is obvious from the north to the south in Beijing zone, representing that the air quality is getting worse from the north to the south; (2) the diurnal variation of daily AQI value reveals interannual periodic trend and a relatively great fluctuating range from 485 to 0. (3) The correlation coefficients of daily AQI mean with average temperature, specific humidity and wind speed are −0.116, −0.073 and −0.192 respectively, displaying that all of the three factors are negatively correlated with AQI and average temperature and wind speed are significantly negatively correlated. The results provide a reference for regional environmental management and pollution prevention and control.